A multidisciplinary approach to the study of slope instability in Derbyshire, with particular reference to Matlock - Dakin, Susan Helen (1989)
This study of slope instability in the Matlock region of Derbyshire uses, and tests the applicability of, a variety of techniques from reconnaissance through to site investigation. The aims have been to (i) provide a greater understanding of landsliding in this area and (ii) produce a critical assessment of the techniques employed.